2022
DOI: 10.3389/fneur.2022.1014346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ischemic stroke diagnosis models based on machine learning

Abstract: BackgroundThe incidence, prevalence, and mortality of ischemic stroke (IS) continue to rise, resulting in a serious global disease burden. The prediction models have a great value in the early prediction and diagnosis of IS.MethodsThe R software was used to screen the differentially expressed genes (DEGs) of IS and control samples in the datasets GSE16561, GSE58294, and GSE37587 and analyze DEGs for enrichment analysis. The feature genes of IS were obtained by several machine learning algorithms, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, the functions of TLR signaling pathways were highly enriched in the high DOCK8 expression group. TLR, as part of the innate immune system, is a bridge between innate and acquired immunity and has been shown to be closely associated with the inflammatory cascade observed after cerebral ischemia (Fadakar et al 2014;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functions of TLR signaling pathways were highly enriched in the high DOCK8 expression group. TLR, as part of the innate immune system, is a bridge between innate and acquired immunity and has been shown to be closely associated with the inflammatory cascade observed after cerebral ischemia (Fadakar et al 2014;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Using machine learning, the researchers assessed five diagnostic algorithms and found that Extreme Gradient Boosting-based models achieved the highest diagnostic value, with impressive results across stroke subcategories. Yang et al [17] address the rising global burden of ischemic stroke (IS) by employing machine learning. It identifies 69 differentially expressed genes associated with IS and reveals immune and inflammatory pathways.…”
Section: State Of the Artmentioning
confidence: 99%
“…The advances in ML have presented opportunities to harness these massive medical datasets to inform medical practice across various domains. In recent years, ML models have been widely used to solve various complex challenges in stroke, such as early stroke detection and thrombolysis decision-making [ 6 , 7 ] neuroimaging analysis [ 8 , 9 ], stroke diagnosis and severity assessment [ 10 , 11 ], candidate selection for therapeutic intervention [ 12 , 13 ], prediction of short- and long-term functional outcomes and prognosis [ [ [14] , [15] , [16] , [17] ]]. Early detection of stroke is a crucial step in ensuring effective treatment and ML has demonstrated significant value in facilitating this process [ 18 ].…”
Section: Introductionmentioning
confidence: 99%